Providing Breastfeeding Support: Experiences from Child-Health Nurses - Grenholm, Emelie Andersson; Söderström, Pernilla; Lindberg, Birgitta (International Journal of Child Health and Nutrition, 2021)
Background: Breastfeeding problems are common during the early period but can often be prevented or overcome with adequate support. Child-health nurses meet almost all children during their first weeks of life and play an important role in promoting breastfeeding and in strengthening parents’ confidence and their belief in their own ability. It is, therefore, important to gain more knowledge about child-health nurses’ experiences. Objective: To describe child-health nurses’ experiences of providing breastfeeding support. Methods: This qualitative study is descriptive with an inductive approach. A purposive sample of eight child-health nurses recruited from district health care centers participated. Data were collected through focus group interviews and analyzed with content analysis. Results: Child-health nurses consider it to be important to provide early breastfeeding support and that early hospital discharge following birth can complicate breastfeeding. Furthermore, the introduction of infant formula and tiny tastes given to the baby can be a barrier to breastfeeding. Parents’ confidence had an effect on breastfeeding, and breastfeeding is promoted by confident parents. Trends and cultural differences have an influence on parents’ attitudes toward breastfeeding. Child-health nurses stated the importance of having a consensus breastfeeding policy. Conclusion and Recommendation: A number of factors affect breastfeeding, and breastfeeding support from child-health nurses is important in the early stages after birth. To conclude, the support must be individually tailored with a focus on the parents’ needs. There is a need for greater cooperation between the maternal care and child-health care staff in order to provide adequate and continuous breastfeeding support throughout the care chain.